Pontocerebellar hypoplasia: clinical case and literature review - Anužis , L.; Buivydas , E.; Petrova , D.; Šukys , M.; Gleiznienė , R. (Neurologijos seminarai, 2019)
Pontocerebellar hypoplasia (PCH) is a group of rare neurodegenerative disorders which start in the intrauterine period and are inherited by autosomal recessive way. Structural changes caused by the mutation include cerebellar hypoplasia or atrophy, microcephalus, and hypoplasia of ventral pons. Clinical signs and symptoms are present in neonatal period or infancy. Progressive microcephalus, sucking and swallowing disorders, jitteriness, generalized clonus, insufficient development of voluntary movements and cognitive functions, and dystonia can be observed. Magnetic resonance imaging (MRI) along with clinical signs and symptoms is very important in suspecting and diagnosing PCH. Most common MRI features include dragonfly configuration cerebellum in coronal sections, absent or severely reduced in size pontine prominence, various degrees of cerebral cortex atrophy, and delayed myelination. To confirm the diagnosis of PCH2A, genetic analysis is required detecting homozygous missense mutation in the TSEN54 gene. In this article we present a clinical case of a neonate whose diagnosis of PCH2A was suspected by clinical symptoms and MRI features and later confirmed by identifying homozygous missense mutation in the TSEN54 gene.